PENGARUH WORK OVERLOAD DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN DENGAN STRES KERJA SEBAGAI VARIABEL MEDIASI PADA PT BPR PADMA - Rohmatika, Vina; Sagung Kartika Dewi, Anak Agung (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.11.TAHUN.2024, 2024)
This study investigates the impact of work overload and conflict on employee performance in the banking industry. The research, conducted at PT BPR Padma, involved 56 employees and used descriptive analysis, classical assumptions, and path analysis. The results showed that work overload negatively impacts employee performance, while work conflict negatively affects performance. Work stress also mediates the effect of work overload and conflict on employee performance. The study aims to inform future research on employee performance by involving more diverse and complex locations. The findings are expected to be used as a reference for companies in making decisions related to improving employee performance. Future research should involve more diverse and complex research locations and involve more respondents.